2019
DOI: 10.18203/2319-2003.ijbcp20194279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical study of efficacy and safety of adapalene 0.1% gel versus benzoyl peroxide 2.5% gel for the treatment of acne vulgaris

Abstract: Background: Acne vulgaris is characterised by comedones, papules, pustules and nodules occurring in a sebaceous distribution. Topical treatments, such as adapalene and benzoyl peroxide, are popular in mild to moderate acne vulgaris. This study was aimed to compare the efficacy and safety of adapalene with benzoyl peroxide in the patients of mild to moderate acne vulgaris.Methods: We planned a randomized, open-labelled, prospective study to compare the efficacy and side effects of adapalene and benzoyl peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(20 reference statements)
3
1
0
Order By: Relevance
“…This could help shape a final consensus regarding the efficacy of these two agents. As per our findings, Benzoyl peroxide was efficacious in 75% of the subjects, comparable to the local and international investigations conducted on the SOC population [ 15 , 16 ]. However, in contrast to a study by Dubey and Amane [ 16 ], our study found no difference in the efficacy of 0.1% adapalene and 4% benzoyl peroxide [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This could help shape a final consensus regarding the efficacy of these two agents. As per our findings, Benzoyl peroxide was efficacious in 75% of the subjects, comparable to the local and international investigations conducted on the SOC population [ 15 , 16 ]. However, in contrast to a study by Dubey and Amane [ 16 ], our study found no difference in the efficacy of 0.1% adapalene and 4% benzoyl peroxide [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…As per our findings, Benzoyl peroxide was efficacious in 75% of the subjects, comparable to the local and international investigations conducted on the SOC population [ 15 , 16 ]. However, in contrast to a study by Dubey and Amane [ 16 ], our study found no difference in the efficacy of 0.1% adapalene and 4% benzoyl peroxide [ 15 , 16 ]. In the follow-up term, benzoyl peroxide demonstrated a prompt deduction of inflammatory lesions identical to other investigations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations